Good Corporate Governance (GCG) di Rumah Sakit - Oberlin Zebua; Denny Tewu (STIE DWI SAKTI BATURAJA, 2023)
Hospital is a comprehensive health service provider institution that provides inpatient services, outpatient services, diagnostic examinations (laboratory, radiology), physiotherapy services, emergency services, pharmacy and others. Hospital services are carried out by various health professionals and have specific roles in providing care to patients. In carrying out services to patients, good governance is needed so that services can run smoothly. Hospitals that implement good governance will have a positive impact on service quality and increase patient satisfaction. This article uses a systematic literature review method and aims to see the positive impact of good corporate governance implemented in hospitals. Literature search related to good corporate governance in hospitals through Google Scholar, and retrieved relevant articles published in 2013-2022. The results obtained in the literature review are (1) the success of implementing Good Corporate Governance in Hospitals is influenced by several factors, namely: organizational culture, company internal control, juridical factors and technical factors. Meanwhile (2) the positive impacts that the hospital gets due to implementing good corporate governance are: increasing employee motivation and performance, reducing the tendency of accounting fraud, increasing patient satisfaction, improving hospital performance.